DOUBLE BLIND CONTROLLED STUDY OF ADDING FOLIC ACID TO FLUOXETINE IN THE TREATMENT OF OCD - (:unkn) unknown (MEDICINSKA NAKLADA, 2019)
Background: Folate is important for the synthesis of serotonin the neurotransmitter which plays a main role in OCD. We, therefore, explored the efficacy of folic acid as add on treatment to fluoxetine in a double blind study among patients with OCD. Subjects and methods: A double blind, 12-week study comparing the efficacy of folic acid as add on treatment and placebo in patients with OCD was conducted on thirty six (36) patients. Patients were randomly assigned to folic acid (5 mg/day) or placebo group in addition to fluoxetine (40 mg/day). After the baseline assessment, on week 2, 4, 6, 8 and 12 assessments were performed by using YBOCS, HAM-D, HAM-A and CGI-S. Serum folate, erythrocyte folate, serum homocysteine and B-12 levels were measured both baseline and the end of study. Results: A mixed model repeated measures ANCOVA on Y-BOCS scores were used to determine the difference between folic acid and placebo groups. No significant differences were found in the ratios of gender or in the mean age, serum folic acid level, erythrocyte folate level, serum homocysteine level and serum B-12 level between the treatment groups at the baseline. Consecutively scores collected over six measurements on YBOCS, HAM-D, HAM-A and CGI showed non-significant differences between folic acid and placebo groups. Conclusion: None of the biological markers of one carbon metabolism were associated with the change in YBOCS scores. It may be assumed that there is no beneficial effect of folic acid addition to fluoxetine in the treatment of OCD.
Keywords: OCD; fluoxetine; serum folate; red cell folate; serum homocysteine; vitamin B-12; MAJOR DEPRESSIVE DISORDER; OBSESSIVE-COMPULSIVE DISORDER; SERUM FOLATE; MONOAMINE METABOLISM; HOMOCYSTEINE LEVELS; CELL FOLATE; VITAMIN-B-12; DEFICIENCY; MTHFR; TETRAHYDROBIOPTERIN